ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU KAYU CEMPAKA PADA INDUSTRI MEBEL DENGAN MENGGUNAKAN METODE EOQ (Studi Kasus Pada UD. Batu Zaman) - Mutiara Simbar; Theodora M. Katiandagho; Tommy F. Lolowang; Jenny Baroleh (COCOS, 2014)
ABSTRACTMutiara Simbar. Analysis of â€œCempakaâ€ Raw Material Inventory Control In Wood Furniture Industry Using EOQMethod (Case Studies at â€œUD. Batu Zamanâ€), Under the guidance of Theodora M. Katiandagho as a Chairman, Tommy Lolowang and Jenny Baroleh as Members.The objective of this research are, a)analyze the optimum volume of raw materials required by â€œUD. Batu zamanâ€ for 2013period, b)analyze the total cost of raw material supply cempaka to be incurred by UD. Batu Zaman for 2013period, c)analyzetime to re-ordering of raw materials cempaka by UD. Batu Zaman for 2013period, d)analyze the amount of safety stock cempaka timber must be provided by UD. Batu Zaman per period in 2013, and e)analyze the inventory control of raw materials Cempaka wood in the furniture industry by using EOQ (Case Studies at UD. Batu zaman).Data was collected from April 2014 - September 2014, The data obtained were primary data and secondary data, Primary data were data collected directly from the company . Secondary data were data that has been arranged in the form of written documents obtained from the company , previous literature as well as from the Internet. Analysis data based on " Economic Order Quantity " to determine the optimal order quantity itâ€™s purchases for with the aim of minimizing inventory costs consist of the cost of ordering and storage costs.The results of the study showed that the purchase of raw materials according to the method of optimal Cempaka Economic Order Quantity during the period of 2013 for one ordering is larger than what the company had done. Optimal raw material purchasing to do the company in 2013 amounted to 4,448 mÂ³ with frequency ordering to do is as much as 2 times, The quantity of safety stock that should be available in warehouse is of 0.24 mÂ³ and a reorder point according to the Economic Order Quantity when 0.603 mÂ³ of wood was available in warehouse inventory. The total cost of inventory to the production process issued by UD. Batu Zaman according to the Economic Order Quantity is less than the total cost of supplies done by company .Key Words : Inventory, Material, Economic Order Quantity.